Housing and Care for Older Women in Australia - Byles, Julie E.; Princehorn, Emily M.; Forder, Peta M.; Rahman, Md Mijanur (Frontiers in Public Health, 2021)
Background: Housing is essential for healthy ageing, being a source of shelter, purpose, and identity. As people age, and with diminishing physical and mental capacity, they become increasingly dependent on external supports from others and from their environment. In this paper we look at changes in housing across later life, with a focus on the relationship between housing and women's care needs. Methods: Data from 12,432 women in the 1921–26 cohort of the Australian Longitudinal Study on Women's Health were used to examine the interaction between housing and aged care service use across later life. Results: We found that there were no differences in access to home and community care according to housing type, but women living in an apartment and those in a retirement village/hostel were more likely to have an aged care assessment and had a faster rate of admission to institutional residential aged care than women living in a house. The odds of having an aged care assessment were also higher if women were older at baseline, required help with daily activities, reported a fall, were admitted to hospital in the last 12 months, had been diagnosed or treated for a stroke in the last 3 years, or had multiple comorbidities. On average, women received few services in the 24 months prior to admission to institutional residential aged care, indicating a potential need to improve the reach of these services. Discussion: We find that coincident with changes in functional capacities and abilities, women make changes to their housing, sometimes moving from a house to an apartment, or to a village. For some, increasing needs in later life are associated with the need to move from the community into institutional residential aged care. However, before moving into care, many women will use community services and these may in turn delay the need to leave their homes and move to an institutional setting. We identify a need to increase the use of community services to delay the admission to institutional residential aged care.